Laying the Foundation for Crassulacean Acid Metabolism (CAM) Biodesign: Expression of the C4 Metabolism Cycle Genes of CAM in Arabidopsis - Lim, Sung Don; Lee, Sojeong; Choi, Won-Gyu; Yim, Won Cheol; Cushman, John C. (Frontiers in Plant Science, 2019)
Crassulacean acid metabolism (CAM) is a specialized mode of photosynthesis that exploits a temporal CO2 pump with nocturnal CO2 uptake and concentration to reduce photorespiration, improve water-use efficiency (WUE), and optimize the adaptability of plants to hotter and drier climates. Introducing the CAM photosynthetic machinery into C3 (or C4) photosynthesis plants (CAM Biodesign) represents a potentially breakthrough strategy to improve WUE while maintaining high productivity. To optimize the success of CAM Biodesign approaches, the functional analysis of individual C4 metabolism cycle genes is necessary to identify the essential genes for robust CAM pathway introduction. Here, we isolated and analyzed the subcellular localizations of 13 enzymes and regulatory proteins of the C4 metabolism cycle of CAM from the common ice plant in stably transformed Arabidopsis thaliana. Six components of the carboxylation module were analyzed including beta-carbonic anhydrase (McBCA2), phosphoenolpyruvate carboxylase (McPEPC1), phosphoenolpyruvate carboxylase kinase (McPPCK1), NAD-dependent malate dehydrogenase (McNAD-MDH1, McNAD-MDH2), and NADP-dependent malate dehydrogenase (McNADP-MDH). In addition, seven components of the decarboxylation module were analyzed within including NAD-dependent malic enzyme (McNAD-ME1, McNAD-ME2), NADP-dependent malic enzyme (McNADP-ME1, NADP-ME2), pyruvate, orthophosphate dikinase (McPPDK), pyruvate, orthophosphate dikinase-regulatory protein (McPPDK-RP), and phosphoenolpyruvate carboxykinase (McPEPCK). Ectopic overexpression of most C4-metabolism cycle components resulted in increased rosette diameter, leaf area, and leaf fresh weight of A. thaliana except for McNADP-MDH, McPPDK-RP, and McPEPCK. Overexpression of most carboxylation module components resulted in increased stomatal conductance and dawn/dusk titratable acidity as an indirect measure of organic acid (mainly malate) accumulation in A. thaliana. In contrast, overexpression of the decarboxylating malic enzymes reduced stomatal conductance and titratable acidity. This comprehensive study provides fundamental insights into the relative functional contributions of each of the individual components of the core C4-metabolism cycle of CAM and represents a critical first step in laying the foundation for CAM Biodesign.